KONSELING INDIVIDU MELALUI CYBER COUNSELING TERHADAP PEMBENTUKAN KONSEP DIRI PESERTA DIDIK - Kw, Sukoco; S., M. Arif Budiman (Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2019)
Low self-concept would interfere with the potential development of learners. Low self-concept can be expected to come from the lack of services for learners. individual counseling services program with the old patterns need to be changed using the model of individual counseling through cyber Counseling. The purpose of this study is to determine the service life of individuals through cyber counseling Counseling, Establishment of the concept of self-pesrta students through cyber Counseling and determine the effect of individual counseling through cyber Conseling towards the formation of self-concept. This type of research is descriptive correlational with non Experimental quantitative approach with product moment correlation analysis. Based on the analysis above, the value of r xy = 0.988. The results are then consulted with r table with the number of respondents N = 30 significant level of 5% turned out to be the value of r xy is bigger than r table is 0.988> 0.361. Individual counseling Counseling Against Cyber Formation Through Self Concept Students in Class XI SMAN 1 Ketanggungan Brebes "are accepted.